Dental remuneration systems - can we pay for prevention? - Listl, Stefan (British dental journal, 2024)
All dental remuneration systems have pros and cons. There is no perfect remuneration system.If the goal is to strengthen prevention of oral diseases, all health system arrangements - including but not limited to the remuneration system - should be aligned towards achieving that goal.Remuneration reforms are complex. Successful reforms require various considerations.
Gesehen am 24.05.2024